2004
DOI: 10.1016/s0272-6386(04)00818-2
|View full text |Cite
|
Sign up to set email alerts
|

Religiosity in a hemodialysis population and its relationship to satisfaction with medical care, satisfaction with life, and adherence

Abstract: Religious beliefs are related strongly to measures of satisfaction with life, whereas religious behaviors are related to satisfaction with medical care. Age is the single most important demographic factor associated with adherence. Because of the complex nature of religiosity, additional investigation is in order.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 0 publications
1
33
1
1
Order By: Relevance
“…In 2004, Berman et al 28 , studying 74 dialysis patients of a center in Philadelphia (United States), reported that patients with high scores in the intrinsic religiosity scale (an aspect that is part of the truly religious individual, who internalizes his/her faith and beliefs in daily life) were more satisfied with life, and those with high scores in the organizational religiosity scale (religious involvement) were more satisfied with medical care. However, no relationship was observed between religiosity and compliance with therapy in that population.…”
Section: Results a N D Discussionmentioning
confidence: 99%
“…In 2004, Berman et al 28 , studying 74 dialysis patients of a center in Philadelphia (United States), reported that patients with high scores in the intrinsic religiosity scale (an aspect that is part of the truly religious individual, who internalizes his/her faith and beliefs in daily life) were more satisfied with life, and those with high scores in the organizational religiosity scale (religious involvement) were more satisfied with medical care. However, no relationship was observed between religiosity and compliance with therapy in that population.…”
Section: Results a N D Discussionmentioning
confidence: 99%
“…Only three studies were identified in the review that explore the relationship between spirituality and survival (Spinale et al, 2008), spirituality and satisfaction with care (Berman et al, 2004) and spirituality and treatment preferences (Song and Hansen, 2009) in patients with ESRD. All were conducted in the USA and used cross-sectional design and valid measures to assess spirituality and religion (as shown in Table 3.5).…”
Section: Spirituality and Survival Satisfaction With Care And Treatmmentioning
confidence: 99%
“…there was a lack of variables to measure relationship with self, others, and nature) and the fact that the scale has not been subject to validity and test re-test reliability means that more studies are needed to establish if it was appropriate to assess spirituality. Berman et al (2004) carried out a survey to examine the relationship between religion and satisfaction with care and adherence to treatment in HD patients (n=74) which found that religiosity was associated with satisfaction with life and medical care (p=.021) but not with adherence to HD treatment. Furthermore, data from a small crosssectional study that was carried out in the USA to examine the relationship between religion and end of life preferences in patients (n=51) receiving HD treatment, demonstrated that there were no associations between importance of spirituality and religion with treatment preferences and acceptance of treatment outcomes (Song and Hanson, 2009).…”
Section: Spirituality and Survival Satisfaction With Care And Treatmmentioning
confidence: 99%
See 1 more Smart Citation
“…sejalan dengan Berman et al (2004) yang menyatakan bahwa religiusitas seseorang yang menjalani hemodialisis sangat berkaitan dengan peningkatan kepuasan hidup pasien.…”
unclassified